Strategi Perubahan pada Perguruan Tinggi Menyikapi Dampak Pandemi Covid 19 - Wijiharta Wijiharta (At-Tauzi : Jurnal Ekonomi Islam, 2020)
The global Covid-19 pandemic has an impact on various sectors including higher education. This study aims to examine the problem of the impact of the pandemic on higher education and the solution strategy, using the literature review method. The conclusion from this literature review is that the problems faced by universities are not only problems of IT facilities and management resources, but there are drastic environmental changes due to the Covid 19 pandemic so that it requires strategic management. Leadership is the main element in strategic change, to provide direction and certainty in the direction of the company, through changing or redefining the mission and vision, as well as strategic re-planning. The implementation of strategies in difficult change situations needs to align with the technical systems, political and cultural values and organizational climate and appropriate control mechanisms.